PENGARUH PENDIDIKAN DAN PENGALAMAN PADA PENDAPATAN RUMAH TANGGA DI INDONESIA - Endang Taufiqurahman (EKUITAS (Jurnal Ekonomi dan Keuangan), 2013)
This research analyse influence of education, job experience, level of parent education and amount of sibling to wages and family income at Indonesian family. Hereafter this research analyse how total family income to measure education and experience role give same explanation than utilizes wage measure. This research will utilize model Mincer Wage Regression on Indonesian family. Analisis's method utilizes IV (Instrumental Variable).  The data will be used is panel data from IFLS (Indonesian Family Life Survey)  which is IFLS 3 years 2000 and IFLS 4 years 2007. Result observation was point out that amount of sibling not significant influence to average education of employment at family, meanwhile parent education is influence signifikan to average education of employment at family. Hereafter average education and experience of employment is significant influence to income and wage at Indonesian family. Then wages measure point out stronger influence than by use of measure total income to measure how education and experience influence to family income at Indonesian.